Backlash against and resistance to feminist peacebuilding - Demirci, Irem (PRIF reports, 2023)
In their PRIF Report the authors focus on the various forms of resistance to and backlash against gender equality and gender-sensitive human rights in peacebuilding processes. Based on 33 interviews with key stakeholders, they explore how peacebuilders understand and perceive resistance to and backlash against the realisation of gender-sensitive human rights in peacebuilding. The report also sheds light on the counter-measures and strategies used by peacebuilders. Finally, the authors discuss the impact of feminist foreign policy on gender-sensitive human rights in peacebuilding.